KAJIAN LAJU INFILTRASI TANAH DAN PENGGUNAANNYA DI DESA NGALANG, KECAMATAN GEDANGSARI, KABUPATEN GUNUNGKIDUL - Fitrah, Dimas Pratama; Budianta, Wawan (KURVATEK, 2023)
Population growth increase makes land management must be done properly. In managing land, one of the most important aspects is soil absorption or infiltration. Factors that affect infiltration include lithology, soil type, and soil physical properties (water content, porosity, pore ratio, saturation degree). Tests were carried out at 32 points in Ngalang Village, Gedangsari District, Gunungkidul Regency. Infiltration rate measurements were performed with turf-tec infiltrometer and calculated using Philips and Kostiakov infiltration model classified by Kohnke's (1968). All parameters are overlaid and graphically correlated to infiltration rate of Philips model which is considered better than Kostiakov. Correlation results show that all parameters have influence on infiltration rate. Soil type has the smallest relationship with R2 value 0.0054, while pore ratio has the largest with R2 value 0.2603. Based on infiltration rate, land use of study area is divided into four, namely agricultural and pasture, plantations, cultivation, and recharge areas